Validation of the Software-Hardware Complex "Rytm" for Measurement of the RR Intervals and Heart Rate Variability Analysis During Exercise and Recovery Period - Lyubomyr Vovkanych; Yuriy Boretsky; Viktor Sokolovsky; Dzvenyslava Berhtraum; Stanislav Kras (OVS LLC, 2021)
The study purpose was estimation of the accuracy of RR time series measurements by SHC "Rytm" and validity of derived heart rate variability (HRV) indexes under physical loads and recovery period. Materials and methods. The participants were 20 healthy male adults aged 19.7 ± 0.23 years. Data was recorded simultaneously with CardioLab CE12, Polar RS800, and SHC "Rytm". Test protocol included a 2 minute step test (20 steps per minute, platform height - 40 cm) with the next 3 minute recovery period. HRV indexes were calculated by Kubios HRV 2.1. Results. The RR data bias in the case of physical loads was -0.06 ms, it increased to 0.09-0.33 ms during the recovery period. The limits of agreement for RR data ranged from 3.7 ms to 22.8 ms, depending on the period of measurements and pair of compared devices. It is acceptable for the heart rate and HRV estimation. The intraclass correlation coefficients (0.62-1.00) and Spearman correlation coefficient (0.99) were high enough to suggest very high repeatability of the data. We found no significant difference (p > 0.05) and good correlation (r = 0.94-1.00) between the majority of HRV indexes, calculated from data of Polar RS800 and SHC "Rytm" in conditions of physical loads (except for LF/HF ratio) and in the recovery period. The only one index (RMSSD) was different (p < 0.05) in case of Polar RS800 and SHC "Rytm" data, obtained in the recovery period. The largest numbers of different HRV indexes have been found during the comparison of CardioLab CE12 and Polar RS800 - RMSSD, pNN50, and SD1. Correlation between HRV indexes (r = 0.81-1.00) was very high in all pairs of devices in all periods of measurements. Conclusions. The SHC "Rytm" appears to be acceptable for RR intervals registration and the HRV analysis during physical loads and recovery period.